Optimization on enzymatic saccharification of pretreated sago hampas for fermentable sugar production - Md Rejab, Rosfariza (2015)
Nowadays, lignocellulosic feedstocks such as corn stover, oil palm biomass, rice straw, sugarcane bagasse and also sago biomass are used for the production of many valuable bioproducts. Sago biomass is a starch and lignocellulosic-based biomass produce from the processing of sago palm. There are three majors sago biomass produced which are sago bark (24 t), sago hampas (50 to 110 t) and sago waste water (300 to 1000 m3) generated daily in the sago processing mills. The waste generated usually discharged to the river without any treatment and this has contributed to high Biological Oxygen Demand (BOD), Chemical Oxygen demand (COD) and suspended solid in the river causing a serious environmental pollution. Sago hampas contained 58% starch, 23% cellulose, 9.2% hemicellulose and also 4% of lignin. In this study, sago hampas were pretreated using the steaming process (autoclave) to remove the starch before proceeded with the enzymatic saccharification to produce fermentable sugar. The saccharification was conducted using a commercial cellulase enzyme (Acremonium Cellulase) and the optimization study was conducted using a two-level factorial design with four parameters which are substrate concentration (1-10%), enzyme concentration (10-50 FPU/g), agitation speed (50-250 rpm) and incubation period (24-96 h). The optimization of enzymatic saccharification of cellulose and hemicellulose of pretreated sago hampas by a cellulase enzyme (10 FPU/g) had produced the highest fermentable sugar (5.94 g/L) at parameter : 10% of substrate concentration, 10 FPU/g of enzyme concentration at 250 rpm of agitation speed in 24 h of incubation period. Through the optimization, the production of fermentable sugar was increased up to 35.2% as the sugar produced before the optimization was about 3.85 g/L.